2D and 3D soil finite/infinite element models: modelling, comparison and application in vehicle-track dynamic interaction. Issue 3 (4th May 2023) - Li, Zheng; Xu, Lei; Wang, Dongli; Niu, Zengjian; Zhao, Yongsheng; Liu, Wei; Zhan, Xinsheng
ABSTRACT: In this work, 2D and 3D vehicle-track-soil (VTS) models are developed in a coupled manner. The VTS system is modelled as an integration of the multi-rigid-body vehicle sub-model, multi-scale finite element ballastless track sub-model and finite/infinite element (FE/IE) soil sub-model, where the IE method is introduced to deal with the boundary condition of the far-field soil. Particularly, the detailed approach for modelling the FE/IE soil sub-model is depicted in the 2D and 3D space domain, respectively. Through comparisons, it is proved that the IE method shows advantages in simulating the soil far-field region by meeting a soil boundary condition. Case studies are conducted to demonstrate the superiority and applicability of this model in improving the computational efficiency. Besides, the influence of vehicle speed on system dynamic performance is revealed, where the soil critical speed derived by the soil Rayleigh surface wave speed is explored by the vehicle-induced vibrations.